1992
DOI: 10.2134/jpa1992.0067
|View full text |Cite
|
Sign up to set email alerts
|

Companion Crop Forage Establishment: Producer Practices and Perceptions

Abstract: There is much interest in fostering cropping practices that reduce pesticide use and enhance soil conservation. A long‐standing practice that addresses these objectives is companion crop establishment of small‐seeded forage legumes. Little information is available regarding current producer practices in companion cropping. A survey was conducted in 1990 of a select sample of Minnesota forage producers to evaluate how they use companion crops, to assess their perceptions of current constraints in companion crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 16 publications
1
37
0
Order By: Relevance
“…Clear‐seeding is a planting method that provides an alternative to using a companion crop. This method provides decreased competition from companion crops and increases in harvested alfalfa yields in the establishment year (Simmons et al, 1992). Herbicides are necessary for weed control and are advantageous for first‐year yields of clear‐seeded alfalfa (Sheaffer et al, 1988).…”
mentioning
confidence: 99%
“…Clear‐seeding is a planting method that provides an alternative to using a companion crop. This method provides decreased competition from companion crops and increases in harvested alfalfa yields in the establishment year (Simmons et al, 1992). Herbicides are necessary for weed control and are advantageous for first‐year yields of clear‐seeded alfalfa (Sheaffer et al, 1988).…”
mentioning
confidence: 99%
“…yield in the year of forage establishment. In a survey of Minnesota forage producers, the most frequent reason selected for using companion crops was soil protection (Simmons et al 1992 The forage yield of dryland alfalfa established with an oat (Avena sativaL.) companion crop in Minnesota was reduced in the first production year compared to direct-seeded alfalfa (Nielsen et al 1981).…”
mentioning
confidence: 99%
“…In fact, greater economic returns have been demonstrated when oat was used as a cover or nurse crop with alfalfa compared to direct seeded alfalfa (17). In a Minnesota survey, 87% of respondents indicated that oat was the companion crop of choice for alfalfa establishment (18).…”
Section: Oat Is a Multi‐use Cropmentioning
confidence: 99%